CHANGES AND CONSEQUENCES OF HUMAN SPIRITUALITY IN THE SPHERE OF GLOBALIZATION - Tulenova Karima Jandarovna; Mamadjonova Marvarid Qurbonnazarovna; Nurtulashev Mansur Juraboevich (European Journal of Humanities and Educational Advancements, 2023)
The article examines the transformation and consequences of the conceptual foundations of human consciousness, spirituality in the sphere of globalization. It has also been shown that we can see that there are external and internal threats to our national morale, each of which poses a danger in its own way